Out behind the desk workplace issues for LGBTQ librarians - Nectoux, Tracy Marie (Gender and sexuality in librarianship, 2011)
"An anthology of personal accounts by librarians and library workers relating experiences of being gay, lesbian, bisexual, transgendered, or queer at work. A broad spectrum of orientations and gender identities are represented, highlighting a range of experiences of being and/or coming out at work"--Provided by publisher.